2020
DOI: 10.17580/gzh.2020.12.02
|View full text |Cite
|
Sign up to set email alerts
|

Gold-tourmaline mineralization in carbonaceous shales of the Kumak deposit (South Ural)

Abstract: The article discusses the geological structure of the Kumak gold ore deposit, confined to the Early Carboniferous Anikhov graben of the East Ural uplift. It is composed of sericite-quartz-carbon and quartz-carbon-tourmaline schists of the Bredy Formation (C1bd). Black shale deposits are carbonaceous type and belong to terrigenous-carbonaceous and silicon-carbonaceous formations. Among the main minerals in shales are noted: quartz, sericite, carbonates, sulfides, tourmaline and carbonaceous matter. The field is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…1). The volcanic sedimentary rocks are cut with numerous intrusive rocks from the Dzhabygasai diorite-plagiogranite-gabbro (pȖ-Ȗį-ȞD 3 d) and Kumak diorite-plagiogranite (įС 1 k) systems [13,17,18].…”
Section: Geological Structurementioning
confidence: 99%
“…1). The volcanic sedimentary rocks are cut with numerous intrusive rocks from the Dzhabygasai diorite-plagiogranite-gabbro (pȖ-Ȗį-ȞD 3 d) and Kumak diorite-plagiogranite (įС 1 k) systems [13,17,18].…”
Section: Geological Structurementioning
confidence: 99%
“…The alteration represents sericite ribbons, recrystallization and segregation of quartz into different thickness veins and strings, tourmalinization, development of carbonate and ferruginization. Rich ore zones are traced at the intersections of the N-S Eastern Anikhovsky Faults and branching disturbed fractures of the N-E and N-W orientation [14].…”
Section: Ore Content Of Carbonaceous Shalementioning
confidence: 99%
“…Here, a score or two gold ore deposits were discovered (East Tykasha, Kommercheskoe, Zabaikal, Baikal, Tsentralnoe, Kumak, Kumak South, etc.). Numerous exploration and geological studies accomplished in this area within nearly a century enabled adjustment of the ore field geology, as well as the metallogeny imaging and reconstruction of deposition of sediments [7,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier exploration campaigns have found that the Carboniferous carbonaceous shales of the East Urals megazone host a number of commercial gold deposits (Kumakskoe, Svetlinskoe, Kamenskoe, Tetechnoe, etc. ), thereby fostering greater research interest in this region [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%